Evolution and genomic insight into methicillin-resistant Staphylococcus aureus ST9 in China. (5th April 2021) - Jiang, Nansong; Wyres, Kelly L; Li, Jun; Feßler, Andrea T; Krüger, Henrike; Wang, Yang; Holt, Kathryn E; Schwarz, Stefan; Wu, Congming
Abstract: Objectives: To reconstruct the evolutionary history and genomic epidemiology of Staphylococcus aureus ST9 in China. Methods: Using WGS analysis, we described the phylogeny of 131 S. aureus ST9 isolates collected between 2002 and 2016 from 11 provinces in China, including six clinical samples from Taiwan. We also investigated the complex structure and distribution of the lsa (E)-carrying multiresistance gene cluster, and genotyped prophages in the genomes of the ST9 isolates. Results: ST9 was subdivided into one major ( n =  122) and one minor ( n =  9) clade. Bayesian phylogeny predicted the divergence of ST9 isolates in pig farming in China as early as 1987, which then evolved rapidly in the following three decades. ST9 isolates shared similar multiresistance properties, which were likely acquired before the ST9 emergence in China. The accessory genome is highly conserved, and ST9 harboured similar sets of phages, but lacked certain virulence genes. Conclusions: Host exchange and regional transmission of ST9 have occurred between pigs and humans. Pig rearing and trading might have favoured gene exchanges between ST9 isolates. Resistance genes, obtained from the environment and other isolates, were stably integrated into the chromosomal DNA. The abundance of resistance genes among ST9 is likely attributed to the extensive use of antimicrobial agents in livestock. Phages are present in the genomes of ST9 and may play a role in the rapid evolution of this ST. Although human ST9 infections are rare, ST9 isolates may constitute a potential risk to public health as a repository of antimicrobial resistance genes.